HUSBAND SUPPORT IN PREGNANT WOMEN WHO TAKE FOLAMIL SUPPLEMENTS FOR INCREASING HEMOGLOBIN LEVELS: A LITERATURE REVIEW - Irmawati Irmawati; Andi Nilawati Usman; Mardiana Ahmad; Nur Aliya Arsyad (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: Folic acid deficiency in pregnancy will cause impaired maturation of erythrocyte nuclei, resulting in the appearance of red blood cells with abnormal shapes and sizes referred to as megaloblastic anemia, further impaired folic acid metabolism will cause impaired DNA replication and cell division processes, and this will affect the work of all cells of the body, including in iron metabolism. Objectives: This study aims to determine the effect of husband support on pregnant women who consume phthalate supplements for increased hemoglobin levels. Design: This research design is a systematic review to find and review articles from databases and theories that are descriptive. Data Sources: Search for articles using the old version of the Mendeley application by entering the keyword